Fitness and compensation - Gagneux, Sébastian (Henry Stewart Talks, 2009)
Concept of Darwinian fitness, Understanding the fitness impact of drug resistance, Mathematical models, Reversal of drug resistance in bacteria, How to measure fitness, The molecular epidemiology approach, Effect of drug resistance mutations, Environment effects on fitness measurements, Effect of strain genetic background, Pre-adapted strain "families", Biogeography of M. tuberculosis, Compensatory evolution, Experimental evidence, Compensation prevents reversion to drug sensitivity, Types of compensatory mutations, Questions for future research, Comparative genomics
Reviewed at 2016/02/26